PENERAPAN LAPORAN KEUANGAN PADA UMKM TOSERBA KELIMUTU WOLOWARU SESUAI STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH - Jadul, Nur Ainun; Marselina, Apriana; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2022)
This study aims to find out how the application of Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM) to the Kelimutu Department Store Business in Wolowaru District, Ende Regency is appropriate or not. The data collection technique used in this study is a qualitative descriptive method. The results of the study show that the Kelimutu Department Store in Wolowaru District, Ende Regency, has not implemented the recording of financial reports in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). In general, the recording and preparation of financial reports carried out by business owners is only in the form of simple financial reports regarding records of incoming and outgoing cash and the final balance. Business owners do not implement the preparation of financial reports starting from general journals, ledgers, trial balances, adjusting entries, trial balance after adjustments, to financial reports which include profit and loss reports, statements of financial position and notes to financial statements. Keywords: